Chosen Aspects of Modernization Processes in EU Countries and in Poland - Classical Point of View - Dworak, Edyta; Malarska, Anna (Comparative Economic Research. Central and Eastern Europe, 2010)
The aim of this paper is an evaluation of changes in a sectoral structure of the employment in EU-countries in time. Against this background there are exposed changes in Polish economy in the period 1997-2008. There were used classical tools of the statistical analysis to illustrate and initially verification the theory of three sectors by A. Fisher, C. Clark i J. Fourastiè, orientated to the evaluation of the modernization process of EU-economies